The hepatic "matrisome" responds dynamically to injury: Characterization of transitional changes to the extracellular matrix in mice. Issue 3 (30th December 2016) - Massey, Veronica L.; Dolin, Christine E.; Poole, Lauren G.; Hudson, Shanice V.; Siow, Deanna L.; Brock, Guy N.; Merchant, Michael L.; Wilkey, Daniel W.; Arteel, Gavin E.
Abstract : The extracellular matrix (ECM) consists of diverse components that work bidirectionally with surrounding cells to create a responsive microenvironment. In some contexts (e.g., hepatic fibrosis), changes to the ECM are well recognized and understood. However, it is becoming increasingly accepted that the hepatic ECM proteome (i.e., matrisome) responds dynamically to stress well before fibrosis. The term "transitional tissue remodeling" describes qualitative and quantitative ECM changes in response to injury that do not alter the overall architecture of the organ; these changes in ECM may contribute to early disease initiation and/or progression. The nature and magnitude of these changes to the ECM in liver injury are poorly understood. The goals of this work were to validate analysis of the ECM proteome and compare the impact of 6 weeks of ethanol diet and/or acute lipopolysaccharide (LPS). Liver sections were processed in a series of increasingly rigorous extraction buffers to separate proteins by solubility. Extracted proteins were identified using liquid chromatography/tandem mass spectrometry (LC‐MS/MS). Both ethanol and LPS dramatically increased the number of matrisome proteins ∼25%. The enhancement of LPS‐induced liver damage by ethanol preexposure was associated with unique protein changes. Conclusion : An extraction method to enrich the hepatic ECM was characterized. The results demonstrate that the hepatic matrisome responds dynamically to both acute (LPS) and chronic (ethanol) stresses, long before more‐dramatic fibrotic changes to the liver occur. The changes to the mastrisome may contribute, at least in part, to the pathological responses to these stresses. It is also interesting that several ECM proteins responded similarly to both stresses, suggesting a common mechanism in both models. Nevertheless, there were responses that were unique to the individual and combined exposures. (Hepatology 2017;65:969‐982).